Place attachment to campus and community green spaces - Worm, Molly (Kansas State University, 2023)
Green spaces, also referred to as natural or built environmental spaces, are growing in popularity across the nation, potentially increasing the forming of person-place bonds also known as place attachments. In this increase, many universities and their surrounding communities incorporate these green spaces into their design, further providing opportunities for research. This study aims to investigate if factors of the individual’s campus environment (e.g., the role of the individual on campus and past use of campus green space), influence their level of place attachment to campus or the community green spaces. An online Qualtrics survey was sent via email to the K-State community (i.e., students and faculty) asking questions related to place attachments. The results showed that place attachment bonds exist at the Kansas State University campus and in Manhattan, KS. However, graduate students presented much lower place attachment scores compared to their university population counterparts highlighting the influence an individual’s role within the population has on an individual’s place attachment. Furthermore, these results provide universities with information on how to allocate their resources among the campus green spaces which could result in higher place attachments among students and faculty in the future.
Keywords: Green spaces